Towards the History of the Use of Church Statistical Files in the Activities of the Geographical Department of the St. Petersburg Academy of Sciences in the Second Part of the 18th Century - Vasilii O. Iakovlev (Вестник Екатеринбургской духовной семинарии)
Using the methods of external and internal criticism the author of this article reveals the information potential of a handwritten document with ecclesiastical statistical content from the 1760s, stored among the scientific and institutional files of the Geographical Department, in the funds of the St. Petersburg branch of the Archive of the Russian Academy of Sciences. The original title of the document is Vedomost’ On the Amount of Eparchies and Lavras, Stavropegic and Diocesan Monasteries, and Hermitages and Churches in the Russian Empire. The source is a neatly executed and filled out table that reflects the main territorial and administrative indicators of the Russian Orthodox Church, presumably as of 1764: the number of dioceses, vicariates, monasteries, as well as a list of all dioceses in Russia with the number of churches in them. Today, the document is a unique example of church-administrative statistics, the formation of which as such occurred only in the 1820s–1830s. Unfortunately, the document is devoid of any accompanying materials, autograph, dating or other record keeping marks that could shed light on the purpose of its creation and the reasons for sending it to the Academy of Sciences, as well as the possible nature of its application and subsequent existence. To interpret the source, the author turns to an analysis of the historical context. He considers briefly the formation of state statistics in Russia in the first half of the 18th century, and the activities of the Geographical Department of the Academy of Sciences, as well as Lomonosov’s, Müller’s and von Schlözer’s activities in areas of geographic and statistical data collection. Based on his analysis, the author makes the assumption that the document could have appeared in connection with the process of centralized collecting geographical information by the Academy of Sciences. In his opinion, the Vedomost’ was drawn up either in the Most Holy Governing Synod, or in the Academy of Sciences itself, on the basis of information specially prepared by the Synod. In addition, the topic of the document is consistent with von Schlözer’s interest in church and state statistics, reflected in his book Neuverändertes Rußland oder Leben Catharinä der Zweyten Kayserinn von Rußland. In this regard, it cannot be ruled out that the document in question also related to thematic preparatory materials for this book. The article is supplemented by the publication of the source itself.